The Role and Importance of Shelters in Overcoming Homelessness - Musa Gürel (İstanbul Üniversitesi Sosyoloji Dergisi)
Homelessness has become an increasingly visible issue in public spaces, both in our country and worldwide, due to the rising number of individuals directly or indirectly affected and its complex relationship with other social problems. When developing social policies and service models for homeless individuals, it is crucial to understand their experiences with these services and the impact of the support they receive. This study aims to comprehensively analyze the effects of shelter services on the process of overcoming homelessness and their role in the transition to permanent housing. The study follows a qualitative research design, with semi-structured interviews conducted with 16 homeless men and 5 shelter staff members in a publicly run men’s shelter in Bursa. The data were analyzed using descriptive analysis under four main themes: reasons for seeking shelter, the scope and evaluation of shelter services, the impact of shelter services on overcoming homelessness, and suggestions for improvement. Findings show that key reasons for seeking shelter include the desire to overcome addiction, distancing oneself from a negative social environment, meeting basic needs, and seeking a safe space. Shelter services were found to provide critical transitional support in addressing homelessness, acting as an intermediary step in short-term interventions. However, long-term and sustainable solutions were deemed more effective in permanently resolving homelessness. The study concludes that shelters should develop service programs tailored to different groups based on age, needs, and circumstances. For long-term success, it is recommended that shelters offer comprehensive rehabilitation services, such as job training, psychological support, family counseling, legal mediation, and addiction treatment, more effectively.